“Community psychosocial accompaniment, community feminisms, and the production of the commons among Mapuche Lafkenche women.” (Palimpsesto, 2026)
This article analyzes the meanings attributed to collaborative community-based psychosocial accompaniment by Mapuche Lafkenche women leaders and the research team, based on an action-research process conducted in Budi, Toltén, and Tirúa, in southern Chile. Drawing on critical community psychology, community feminisms, and decolonial thought, the study examines accompaniment not as a technical intervention strategy, but as a political practice of care, leadership strengthening, intergenerational transmission, and commons-making. Findings show that accompaniment contributes to sustaining community life, strengthening networks of trust, and expanding Indigenous women’s capacity for political action, thus constituting a situated feminist practice and a form of collective production of the commons.
Keywords: Community-based psychosocial accompaniment; community feminisms; care; the commons; Indigenous women’s leadership; critical community psychology; decolonial approach